TECTONIC ORIGIN OF THE APSHERON THRESHOLD IN THE CASPIAN SEA - Khain V.E.; Gadjiev A.N.; Kengerli T.N. (My University, 2007)
The Apsheron (Absheron) Threshold is a seamount crowned by small islands and banks that separates the Middle Caspian (Derbent) and South Caspian basins of the Caspian Sea. It is traditionally considered as a link between orogenic structures of the Greater Caucasus and Kopetdag. As is shown below, the tectonic nature of this relatively heterogeneous structure is ambiguous. The purpose of this paper is to consider this problem.